Who Must You Trust? - WADLOW, THOMAS (Communications of the ACM, 2014)
The article discusses the reported importance of trust in a work environment as of July 2014, focusing on Neal Stephenson's book "The Diamond Age," constructed societies (phyles) based on extreme trust in one's fellow members, and the Heartbleed OpenSSL computer virus. According to the article, systems administrators (SAs) are at the heart of everything that works on the Internet. Former U.S. National Security Agency SA Edward Snowden is mentioned, along with former network administrator Terry Childs' arrest in 2008.